Nano cubic boron nitride toughened diamond compact as well as preparation method and application thereof
By adding nanocubic boron nitride and cobalt powder to the diamond composite sheet, the toughening frame and D-D bond connection are formed, which solves the cracking problem of diamond composite sheet during fine particles synthesis, improves its toughness and wear ratio, and meets the needs of high-precision processing.
Patent Information
- Application Number
- CN202311307887.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
AI Technical Summary
Diamond composite sheets have hard and brittle cracking problems when synthesizing fine particles. The material has high stress and is extremely prone to cracking, making it difficult to meet the needs of high-precision processing.
By adding nanocubic boron nitride and cobalt powder, a cubic boron nitride frame is formed, combining the auxiliary effect of cobalt, the brittleness of diamond is reduced, its toughness is improved, and D-D bond connection is formed in high-temperature and high-pressure treatment to enhance the polycrystalline structure of diamond.
Effectively prevent the cracking of nanostructured diamond composite sheets, improve their toughness and wear ratio, meet the needs of high-precision processing, and reduce processing costs.
Smart Images

Figure CN119800187A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diamond composite sheets, and in particular to a nano cubic boron nitride toughened diamond composite sheet and a preparation method and application thereof. Background Art
[0002] Diamond composite sheet is a superhard material composite sheet, which is mainly composed of diamond and polymerized on the surface of cemented carbide substrate. It has the characteristics of high hardness and good wear resistance. It is widely used in industries such as oil drilling, geological exploration, coal drilling and mining drill bits and mechanical processing tools, including commonly used machine tool turning tools, machining drill bits, frame processing milling cutters and copy milling cutters. Affected by processing needs, the precision requirements of workpieces are getting higher and higher, and the demand for superhard material tools is also getting higher and higher. Generally speaking, the finer the particle size of the diamond in the superhard material composite sheet, the smaller the surface roughness of the workpiece processed as a tool material, and the more it can meet the purpose of cutting instead of grinding in the non-ferrous metal or inorganic material processing industry, thereby saving the processing industry's requirements for high precision and processing efficiency, and reducing the time cost and labor cost of processing.
[0003] At present, the synthesis of diamond composite sheets mainly uses three black metal catalysts, iron, cobalt and nickel, to transform diamond particles into polycrystals through high temperature and high pressure. However, as the size of diamond particles decreases, the hardness and brittleness cracking problem of diamond composite sheets becomes more serious. The main problem with synthesizing fine-grained diamond composite sheets is that the material has high stress and brittleness, and is extremely easy to crack. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a nano cubic boron nitride toughened diamond composite sheet and its preparation method and application. The nano cubic boron nitride toughened diamond composite sheet provided by the present invention can effectively prevent the nanostructured diamond composite sheet from cracking.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a nano cubic boron nitride toughened diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials comprising the following mass percentages:
[0007]
[0008]
[0009] Preferably, the particle size of the diamond powder is 300 to 1000 nm;
[0010] The diameter of the cubic boron nitride sheet is 5 to 500 nm;
[0011] The particle size of the cobalt powder is 5 to 500 nm;
[0012] The particle size of the tantalum powder is 5 to 500 nm.
[0013] Preferably, the cemented carbide substrate is made of YG16.
[0014] The present invention provides a method for preparing the nano cubic boron nitride toughened diamond composite sheet, comprising the following steps:
[0015] Diamond micro powder, cubic boron nitride, cobalt powder and tantalum powder are ball-milled and mixed to obtain mixed micro powder;
[0016] placing the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain reduced mixed micropowder;
[0017] Pressing the cemented carbide sheet and the reduced mixed micro powder into a pre-assembled composite sheet;
[0018] Under vacuum conditions, the pre-assembled composite sheet is heated, purified and shaped to obtain a purified and shaped composite sheet;
[0019] The purified and shaped composite sheet is subjected to high temperature and high pressure treatment to obtain a nano cubic boron nitride toughened diamond composite sheet.
[0020] Preferably, the ball milling mixing rate is 120-180 r / min, and the time is 3-8 h.
[0021] Preferably, the temperature of the reduction reaction is 350-950° C., and the time is 0.5-3 h; and the pressure of hydrogen in the hydrogen atmosphere is 0.02-0.1 MPa.
[0022] Preferably, the pressing pressure is 3 to 5 tons and the time is 3 to 30 seconds.
[0023] Preferably, the temperature of the heating, purification and shaping is 600-1100°C, and the holding time is 1-3h;
[0024] The vacuum degree of the vacuum condition is 10 -4 ~10 -2 Pa.
[0025] Preferably, the temperature of the high temperature and high pressure treatment is 1550-1750° C., the pressure is 5-6.5 GPa, and the heat and pressure holding time is 12-25 min.
[0026] The present invention provides application of the nano cubic boron nitride toughened diamond composite sheet in cutting tools.
[0027] The present invention provides a nano cubic boron nitride toughened diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials comprising the following mass percentages: 86-96.5% diamond micropowder; 2-6% cubic boron nitride; 1-5% cobalt powder; 0.5-3% tantalum powder. The present invention adds cubic boron nitride and cobalt powder, and cubic boron nitride reacts with cobalt to form a cubic boron nitride framework, the framework hardness is lower than diamond but higher than cobalt, and with the assistance of cobalt, the brittleness of cubic boron nitride is also lower than diamond, so that the diamond polycrystal has a toughening effect; cobalt powder and tantalum powder serve as catalysts to reduce the synthesis pressure and temperature in the synthesis of diamond polycrystals. The nano cubic boron nitride toughened diamond obtained by the present invention has good toughness and can effectively avoid the cracking of the nanostructured diamond composite sheet.
[0028] The present invention provides a method for preparing the nano cubic boron nitride toughened diamond composite sheet. During the high temperature and high pressure treatment, the diamond micropowder forms polycrystals, and DD bonds are formed between the diamond micropowder particles, so that the diamond particles are connected into sheets. The preparation method provided by the present invention is simple to operate, has strong applicability, can improve the yield rate of the diamond composite sheet, and is easy to realize industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a microstructure diagram of the 850 nanometer diamond composite sheet obtained in Example 1. DETAILED DESCRIPTION
[0030] The present invention provides a nano cubic boron nitride toughened diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot-pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials comprising the following mass percentages:
[0031]
[0032] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0033] In the present invention, the cemented carbide is preferably YG16. In the present invention, the thickness of the cemented carbide is preferably 3 to 6 mm, more preferably 4 to 5 mm.
[0034] In the present invention, the thickness of the superhard material on the surface of the cemented carbide is preferably 0.3-0.9 mm, more preferably 0.6 mm.
[0035] In terms of mass percentage, the superhard material comprises 86-96.5% diamond powder, preferably 88-92%, and more preferably 90%. In the present invention, the particle size of the diamond powder is preferably 300-1000nm, more preferably 500-800nm, and more preferably 600-700nm.
[0036] In terms of mass percentage, the superhard material comprises 2-6% cubic boron nitride, preferably 3-4%, more preferably 5%. In the present invention, the flake diameter of the cubic boron nitride is preferably 5-500nm, more preferably 50-400nm, and further preferably 100-300nm.
[0037] In terms of mass percentage, the superhard material comprises 1-5% cobalt powder, preferably 2-4%, more preferably 3%. In the present invention, the particle size of the cobalt powder is preferably 5-500nm, more preferably 50-400nm, and further preferably 100-300nm.
[0038] In terms of mass percentage, the superhard material comprises 0.5-3% tantalum powder, preferably 1-2.5%, more preferably 1.5-2%. In the present invention, the particle size of the tantalum powder is preferably 5-500nm, more preferably 50-400nm, and further preferably 100-300nm.
[0039] The present invention provides a method for preparing the nano cubic boron nitride toughened diamond composite sheet, comprising the following steps:
[0040] Diamond micro powder, cubic boron nitride, cobalt powder and tantalum powder are ball-milled and mixed to obtain mixed micro powder;
[0041] placing the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain reduced mixed micropowder;
[0042] Pressing the cemented carbide sheet and the reduced mixed micro powder into a pre-assembled composite sheet;
[0043] Under vacuum conditions, the pre-assembled composite sheet is heated, purified and shaped to obtain a purified and shaped composite sheet;
[0044] The purified and shaped composite sheet is subjected to high temperature and high pressure treatment to obtain a nano cubic boron nitride toughened diamond composite sheet.
[0045] The present invention ball-mills diamond micropowder, cubic boron nitride, cobalt powder and tantalum powder to obtain mixed micropowder. In the present invention, the ball milling is preferably wet ball milling; the ball milling medium of the ball milling mixture is preferably stainless steel balls, and the dispersion medium is preferably an organic solvent, and the organic solvent is preferably one or more of ethanol, ethylene glycol, propanol, acetone and n-heptane.
[0046] In the present invention, the ball milling mixing rate is preferably 120 to 180 r / min, more preferably 150 r / min; the time is preferably 3 to 8 h, more preferably 5 h.
[0047] After obtaining the mixed micropowder, the present invention places the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain a reduced mixed micropowder. In the present invention, the pressure of the hydrogen in the hydrogen atmosphere is preferably 0.02 to 0.1 MPa, and more preferably 0.04 to 0.08 MPa. In the present invention, the temperature of the reduction reaction is preferably 350 to 950°C, and more preferably 600 to 700°C; the time is preferably 0.5 to 3h, and more preferably 1 to 2h. In the present invention, cobalt powder and tantalum powder are used as catalysts, which are easily oxidized to oxides, reducing the activity of the catalyst. The present invention can reduce the oxidized metal catalyst through the reduction reaction, thereby improving the catalytic activity of cobalt powder and tantalum powder.
[0048] After obtaining the reduced mixed micropowder, the present invention presses the cemented carbide sheet and the reduced mixed micropowder to obtain a pre-assembled composite sheet. In the present invention, the press molding is preferably performed in a niobium cup. Specifically, the present invention preferably spreads the reduced mixed micropowder in the niobium cup, covers it with a cemented carbide sheet, matches a suitable molybdenum cup as a lid, and presses it. In the present invention, based on a niobium cup with a diameter of 35 mm, the mass of the reduced mixed micropowder used for a single press molding is preferably 3 to 5 g, and more preferably 4 g.
[0049] The present invention preferably uses a hydraulic press to perform the compression molding. In the present invention, the compression molding pressure is preferably 3 to 5 tons, more preferably 5 tons; the time is preferably 3 to 30 seconds, more preferably 10 to 20 seconds. In the present invention, the compression molding is preferably performed indoors at room temperature and a humidity of less than 45%.
[0050] After obtaining the pre-assembled composite sheet, the present invention heats, purifies and shapes the pre-assembled composite sheet under vacuum conditions to obtain a purified and shaped composite sheet. The present invention preferably performs the heating, purifying and shaping in a vacuum furnace. In the present invention, the vacuum degree of the vacuum condition is preferably 10 -4 ~10 -2 Pa, more preferably 10 -4 Pa. In the present invention, the temperature of the heating, purification and shaping is preferably 600-1100°C, more preferably 700-800°C; the holding time is preferably 1-3h, more preferably 1.5h. In the present invention, the heating rate to the heating, purification and shaping temperature is preferably 20°C / min. In the present invention, during the heating, purification and shaping process, the air adsorbed in the powder is released under vacuum and high temperature, and the adhesive is slightly melted at high temperature to shape the material from powder to block.
[0051] After obtaining the purification and shaping composite sheet, the present invention performs high temperature and high pressure treatment on the purification and shaping composite sheet to obtain a nano cubic boron nitride toughened diamond composite sheet. The present invention preferably performs the high temperature and high pressure treatment on a six-sided top press. In the present invention, the temperature of the high temperature and high pressure treatment is preferably 1550-1750°C, more preferably 1600°C; the pressure is preferably 5-6.5GPa, more preferably 5.5GPa; the heat preservation and pressure holding time is preferably 12-25min, more preferably 15min. In the present invention, the heating rate of the high temperature and high pressure treatment is preferably 400°C / min, and the pressure increase rate is preferably 10GPa / min. In the present invention, during the high temperature and high pressure treatment, the diamond powder forms polycrystals, and DD bonds are formed between the diamond powder particles, so that the diamond particles are connected into sheets.
[0052] The present invention provides the use of the nano cubic boron nitride toughened diamond composite sheet in a tool. In the present invention, the tool is preferably one or more of a machining tool, an integral diamond milling cutter, an integral diamond drill bit, a micro-drill bit and a twist milling cutter.
[0053] The nano cubic boron nitride toughened diamond composite sheet and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0054] Example 1
[0055] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0056] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0057] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0058] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0059] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0060] The microstructure of the obtained 850 nanometer diamond composite sheet is shown in Figure 1 As shown by Figure 1 It can be seen that the size of the gray-black diamond is about 850nm, there is no obvious boundary between the diamond particles, and the diamond-specific DD bonding is formed between the particles. The white dots around the diamond particles are catalysts.
[0061] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.3×10 4 .
[0062] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.54 mm, showing a dimple fracture.
[0063] Example 2
[0064] (1) 92.5 g of 500 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0065] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0066] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0067] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0068] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as a 500 nano-diamond composite sheet.
[0069] The wear ratio of the obtained 500 nanometer diamond composite sheet was tested using "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.1×10 4 .
[0070] The impact toughness of the obtained 500 nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.62 mm, showing a dimple fracture.
[0071] Example 3
[0072] (1) 92.5 g of 850 nm diamond powder, 5 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0073] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0074] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0075] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0076] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0077] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.1×10 4 .
[0078] The impact toughness of the obtained 850 nano-diamond composite sheet was tested using an impact toughness testing machine. The nano-diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.41 mm, showing a dimple fracture.
[0079] Example 4
[0080] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0081] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0082] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0083] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0084] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 6.0 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0085] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.4×10 4 .
[0086] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.51 mm, showing a dimple fracture.
[0087] Example 5
[0088] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0089] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0090] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0091] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0092] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1550°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0093] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.1×10 4 .
[0094] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.67 mm, showing a dimple fracture.
[0095] Comparative Example 1
[0096] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel pot with an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved with a 100-mesh sieve to obtain a mixed powder.
[0097] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0098] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0099] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0100] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-free cubic boron nitride toughened diamond composite sheet, recorded as an 850 nano diamond composite sheet.
[0101] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.4×10 4 .
[0102] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.92 mm, showing a dimple fracture.
[0103] Comparative Example 2
[0104] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm iron-nickel alloy powder were ball-milled at 120 r / min for 3 hours in a stainless steel tank containing an organic solvent. The mixture was dried at 80° C. and sieved through a 100-mesh sieve to obtain a mixed powder.
[0105] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0106] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0107] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0108] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0109] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.9×10 4 .
[0110] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.85 mm, showing a dimple fracture.
[0111] Comparative Example 3
[0112] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0113] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0114] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0115] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0116] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 4.5 GPa, a temperature of 1600°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0117] (6) 90% of the samples’ polycrystalline layers were graphitized and turned black, and only a few samples were intact.
[0118] The complete sample was selected and the wear ratio of the obtained 850 nanometer diamond composite sheet was tested using "JB / T 3235-2013: Determination Method of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 1.6×10 4 .
[0119] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 2.61 mm, showing a dimple fracture.
[0120] Comparative Example 4
[0121] (1) 92.5 g of 850 nm diamond powder, 3 g of 200 nm cubic boron nitride, 3 g of 200 nm cobalt powder, and 1.5 g of 200 nm tantalum powder were ball-milled in a stainless steel tank containing an organic solvent at a rate of 120 r / min for 3 hours, dried at 80° C., and sieved through a 100-mesh sieve to obtain a mixed powder.
[0122] (2) The mixed micropowder is reduced in hydrogen at 600° C. for 1 h and the hydrogen pressure is 0.08 MPa to obtain reduced mixed micropowder.
[0123] (3) 4 g of reduced mixed micro powder was spread flatly into a niobium cup with a diameter of 35 mm and covered with a 3 mm thick cemented carbide (grade YG16). A suitable molybdenum cup was matched as a lid. The powder was compacted using a hydraulic press with a pressure of 5 tons to obtain a pre-assembled composite sheet.
[0124] (4) Place the preassembled composite sheet into a vacuum furnace and heat it for 10 -4 The purified and shaped composite sheet was obtained by heating at 700°C in vacuum and keeping the temperature for 1.5 hours.
[0125] (5) The purified and shaped composite sheet is matched with a conventional suitable carbon salt tube and pyrophyllite block, and subjected to high temperature and high pressure treatment in a six-sided top press, with a pressure of 5.5 GPa, a temperature of 1500°C, and a heat preservation and pressure holding time of 15 min to obtain a nano-cubic boron nitride toughened diamond composite sheet, recorded as 850 nano-diamond composite sheet.
[0126] The wear ratio of the 850 nanometer diamond composite sheet was tested using the "JB / T 3235-2013: Determination of Wear Ratio of Polycrystalline Diamond". The wear ratio of the nanometer diamond composite sheet obtained by the silicon carbide grinding wheel test was 2.1×10 4 .
[0127] The impact toughness of the obtained 850 nanometer diamond composite sheet was tested using an impact toughness testing machine. The 850 nanometer diamond composite sheet was processed by electric spark wire cutting into a sample with a diameter of 13.8 mm. The weight height was 13.5 cm, the weight was 0.6 kg, the single impact energy was 0.7938 J, and after 30 continuous impacts, the edge damage length was 1.76 mm, showing a dimple fracture.
[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A nano cubic boron nitride toughened diamond composite sheet, comprising a cemented carbide substrate and a superhard material hot pressed on the surface of the cemented carbide substrate, wherein the superhard material is prepared from raw materials including the following mass percentages:
2. The nano cubic boron nitride toughened diamond composite sheet according to claim 1, characterized in that: The particle size of the diamond powder is 300 to 1000 nm; The diameter of the cubic boron nitride sheet is 5 to 500 nm; The particle size of the cobalt powder is 5 to 500 nm; The particle size of the tantalum powder is 5 to 500 nm.
3. The nano cubic boron nitride toughened diamond composite sheet according to claim 1, characterized in that: The material of the cemented carbide substrate is YG16.
4. The method for preparing the nano cubic boron nitride toughened diamond composite sheet according to any one of claims 1 to 3, comprising the following steps: Diamond micro powder, cubic boron nitride, cobalt powder and tantalum powder are ball-milled and mixed to obtain mixed micro powder; placing the mixed micropowder in a hydrogen atmosphere to perform a reduction reaction to obtain reduced mixed micropowder; Pressing the cemented carbide sheet and the reduced mixed micro powder into a pre-assembled composite sheet; Under vacuum conditions, the pre-assembled composite sheet is heated, purified and shaped to obtain a purified and shaped composite sheet; The purified and shaped composite sheet is subjected to high temperature and high pressure treatment to obtain a nano cubic boron nitride toughened diamond composite sheet.
5. The preparation method according to claim 4, characterized in that: The ball milling mixing speed is 120-180 r / min, and the time is 3-8 h.
6. The preparation method according to claim 4, characterized in that: The temperature of the reduction reaction is 350-950° C., and the time is 0.5-3 h; the pressure of hydrogen in the hydrogen atmosphere is 0.02-0.1 MPa.
7. The preparation method according to claim 4 or 6, characterized in that: The pressing pressure is 3 to 5 tons and the pressing time is 3 to 30 seconds.
8. The preparation method according to claim 4, characterized in that: The temperature of the heating, purification and shaping is 600-1100°C, and the insulation time is 1-3h; The vacuum degree of the vacuum condition is 10 -4 ~10 -2 Pa.
9. The preparation method according to claim 4 or 8, characterized in that: The temperature of the high temperature and high pressure treatment is 1550-1750° C., the pressure is 5-6.5 GPa, and the heat preservation and pressure holding time is 12-25 minutes.
10. Use of the nano-cubic boron nitride toughened diamond composite sheet according to any one of claims 1 to 3 or the nano-cubic boron nitride toughened diamond composite sheet according to any one of claims 4 to 9 in cutting tools.